Synchronous adrenocortical carcinoma and ovarian malignant mixed germ cell tumor: A case report and literature review. Issue 20 (May 2018) - He, Ying; Xu, Lian; Li, Qingli; Feng, Min; Wang, Wei
Abstract: Rationale: Adrenocortical carcinoma (ACC) is an endocrine malignancy with poor prognosis, which commonly arises in a sporadic manner, but may also become a part of a familial syndrome. ACC rarely arises simultaneously with other malignant tumors. Patient concerns: We report a case of a 29-year-old woman with ACC synchronously followed by an ovarian malignant mixed germ cell tumor. We describe the clinical, histopathological, and immunohistochemical findings and review the English literatures. So far, as we know, the patient presented here is the first case with synchronous malignant tumors of the adrenal gland and ovary. Diagnoses: She was diagnosed with ovarian malignant mixed germ cell tumor with admixture of dysgerminoma and yolk sac tumor after ACC. Interventions: The left adrenal tumor was resected laparoscopically on April 28, 2017. A total laparoscopic hysterectomy with unilateral (right) adnexectomy was performed on November 11, 2017. Outcomes: Up to now, illness condition has not progressed. Patient is free of disease at 3 months of follow-up. Lessons: This is the first report in English literature about coexistence of ACC with ovarian malignant mixed germ cell tumor and the sixteenth case that presents a synchronous tumor associated with a sporadic ACC. This case reminds us that a comprehensive examination of patients with ACC is necessary to identify a possible synchronous tumor.